2004
DOI: 10.1039/b314938m
|View full text |Cite
|
Sign up to set email alerts
|

Studies on selective adsorbents for oxo-anions. Nitrate ion-exchange properties of layered double hydroxides with different metal atoms

Abstract: Layered double hydroxides (LDHs) with different kinds of metal ions (Mg-Al, Co-Fe, Ni-Fe, and Mg-Fe) in the brucite layers were prepared and their anion exchange properties were studied by measurements of distribution coefficient (K d ) and ion exchange capacity. The basal spacing of LDHs varied depending on the kind of metal ions in the brucite layer. A relatively high K d value for NO 3 2 ions was observed on Ni-Fe type LDHs, and a markedly high K d value for the hydrothermally-treated Ni-Fe type LDHs (Ni-Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 31 publications
2
53
0
6
Order By: Relevance
“…It is therefore very questionable whether LDHs could be used as nitrate adsorbents. However, several recent studies have reported that certain LDHs with specific compositions [21][22][23][24][25][26][27][28] show high selectivity for nitrate ions. Those reports, however, did not address the question of whether only the nitrate anion among monovalent anions and anions of low charge densities has a high affinity for LDHs under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore very questionable whether LDHs could be used as nitrate adsorbents. However, several recent studies have reported that certain LDHs with specific compositions [21][22][23][24][25][26][27][28] show high selectivity for nitrate ions. Those reports, however, did not address the question of whether only the nitrate anion among monovalent anions and anions of low charge densities has a high affinity for LDHs under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peak at 1,380 cm -1 was observed in LDH-NO 3 , which is attributable to the symmetric vibration of the interlayer nitrate anion (Figure 1Ba). [28][29][30][31]36] LDH-Fe(CN) 6 showed that an absorption peak at 1,380 cm [25,37,38] SEM images of the LDH-NO 3 and LDH-Fe(CN) 6 are shown in Figure 1C. As can be seen, the rosette aggregation for LDH-NO 3 was observed (Figure 1Ca).…”
Section: Physical Measurementsmentioning
confidence: 88%
“…The d 003 = 8.8 Å and a = 3.04 Å were consistent with well-known LDHs containing the nitrate anion (Table 1). [23,24,[28][29][30][31] 6 , and (c) LDH-PB. BS is basal spacing.…”
Section: Physical Measurementsmentioning
confidence: 99%
“…Harmful anions such as phosphate, arsenic and nitrate ions can be absorbed in the interlayers of LDHs [121][122][123]. We focused on preparing multifunctional composites with adsorption properties, which can be used to simultaneously remove harmful cations and anions.…”
Section: Zeolite/ldh Compositesmentioning
confidence: 99%